Mass cytometry reveals cladribine-induced resets among innate lymphoid cells in multiple sclerosis - F. T. Aglas-Leitner; P. Juillard; A. Juillard; S. N. Byrne; S. Hawke; G. E. Grau; F. Marsh-Wakefield (Scientific Reports, 2022)
Abstract Here we present a comprehensive mass cytometry analysis of peripheral innate lymphoid cell (ILC) subsets in relapsing/remitting MS (RRMS) patients prior to and after onset of cladribine tablets (CladT). ILC analysis was conducted on CyTOF data from peripheral blood mononuclear cells (PBMC) of MS patients before, 2 and 6 months after onset of CladT, and non-MS controls. Dimensionality reduction was used for immunophenotyping ILC subsets. CladT reduced all ILC subsets, except for CD56bright NK cells and ILC2. Furthermore, CD38+ NK cell and CCR6+ ILC3 were excluded from CladT-induced immune cell reductions. Post-CladT replenishment by immature ILC was noted by increased CD5+ ILC1 proportions at 2 months, and boosted CD38−CD56bright NK cell numbers at 6 months. CladT induce immune cell depletion among ILC but exclude CD56bright NK cells and ILC2 subsets, as well as CD38+ NK cell and CCR6+ ILC3 immunophenotypes. Post-CladT ILC expansions indicate ILC reconstitution towards a more tolerant immune system phenotype.